Analysis of Factors Related to The Incidence of Anemia in Adolescent Girls in Wetland Areas - Meitria Syahadatina Noor; Andini Octaviana Putri; Mufatihatul Azizah Nisa; Setyo Teguh Waluyo; Fakhriyah Fakhriyah (Jurnal Berkala Kesehatan, 2025)
Adolescents are a vulnerable group to nutritional problems due to their rapid growth and development, which require increased nutrient intake. One of the most common nutritional problems among adolescents in South Kalimantan Province is anemia, with a prevalence of 21.60%, and 23.54% in Banjar Regency. This study aims to analyze the relationship between knowledge, attitudes, compliance with iron tablet supplementation, and eating habits, and the incidence of anemia among adolescent girls. This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 47 adolescents selected using a total sampling technique. Data were collected using questionnaires to assess independent variables (knowledge, attitudes, compliance with iron supplementation, and eating habits), and a hemoglobinometer was used to measure hemoglobin (Hb) levels to determine anemia status. Data were analyzed using univariate analysis with frequency distribution tables and bivariate analysis using the Chi-square test. The results showed no significant relationship between knowledge (p = 0.246), attitudes (p = 1.000), compliance with iron supplementation (p = 1.000), and eating habits (p = 0.375) and the incidence of anemia among adolescent girls. However, descriptive findings indicate that poor eating habits tend to increase the risk of anemia.